The Influence of Learning Model and Student Self-Concept Toward the Mathematical Problem-Solving Ability (Experimental Study on Students of Tangerang City State Junior High School) - Dewi, Ruby Fauziyah Andam; Noornia, Anton; Wiraningsih, Eti Dwi (Universitas Islam Raden Intan Lampung, INDONESIA, 2018)
This study aims to determine the effect of Conventional Model and the Missouri Mathematics Project (MMP) learning Model with self-concept on mathematical problem- solving abilities of junior high school students. The design of this study was experimental and control group post-test design. The method used is the quasi-experimental method using treatment by level 2x2 design. The experimental class was given the MMP learning model treatment while the control class was treated with conventional model. The samples of this study were 48 seventh grade students. The instruments used were self-concept questionnaires and a test of mathematical problem-solving abilities.Technique of analysis used was two-ways ANOVA. The results of this study show that the MMP learning model has a syntax that is able to empower mathematical problem-solving abilities compared to conventional learning model. Students who have a positive self-concept or students who have a negative self-concept are more suitable to be treated with the MMP learning model than conventional learning model.